Advances in heterocyclic chemistry. 119 : heterocyclic chemistry in the 21st century : a tribute to Alan Katritzky - Scriven, Eric F. V.; Ramsden, Christopher A., 1946-; Katritzky, Alan R.; ScienceDirect eBooks (Waltham, MA : Academic Press, 2016)
Advances in Heterocyclic Chemistry is the definitive series in the field-one of great importance to organic chemists, polymer chemists, and many biological scientists. Because biology and organic chemistry increasingly intersect, the associated nomenclature also is being used more frequently in explanations. Written by established authorities in the field from around the world, this comprehensive review combines descriptive synthetic chemistry and mechanistic insight to yield an understanding of how chemistry drives the preparation and useful properties of heterocyclic compounds.
Includes bibliographical references and index.
Vendor-supplied metadata.
Elsevier
Keywords: Heterocyclic chemistry -- 21st century; SCIENCE / Chemistry / Organic; Heterocyclic chemistry; 2000-2099; Electronic books